Integration of optical waveguide on pneumatic balloon actuator for flexible scanner in endoscopic imaging diagnosis applications. (2nd August 2016) - Konishi, Satoshi; Kobayashi, Taizo; Muramatsu, Yoko
Abstract: This paper reports a flexible scanner consisting of a scanning actuator and optical waveguides for medical imaging applications such as endoscopic fluorescence imaging diagnosis. The 0.3-mm-thick and 5-mm-wide functional scanner was designed to be smaller enough than the 10 mm-diameter of channel of endoscope. The proposed device can be used to introduce an excitation light into the abdominal cavity or digestive tract. A pneumatic balloon actuator (PBA) consisting of polydimethylsiloxane (PDMS) is used as the scanning actuator for the scanner in consideration of its small, soft, and safe features. The SU-8 optical waveguides with high refractive index ( n SU-8 = 1.575) are integrated onto the PBA structure made of PDMS with a lower refractive index ( n PDMS = 1.405). Excitation light at a wavelength of 405 nm is transmitted through an optical fiber to the SU-8 waveguides. The outgoing light from the waveguide can be scanned by the bending motion of the PBA. The waveguide functions as a detector as well. Our developed device has successfully scanned, excited, and detected light from fluorescence beads at a wavelength of 540 nm distributed in a pseudo-tissue. Abstract :